DAMPAK TEKNOLOGI OFF-SEASON TERHADAP PENDAPATAN USAHATANI MANGGA GEDONG GINCU (MANGIFERA INDICA L. VAR. GEDONG GINCU) - Tohir, Tohir; Ayu Andayani, Sri; Umyati, Sri (Journal of Sustainable Agribusiness, 2025)
Gedong Gincu mango is a leading horticultural commodity in Majalengka Regency with high economic value. However, its dependency on seasonal harvests leads to price fluctuations and unstable farmer incomes. The Off-Season technology emerges as a solution to extend the production period by inducing mango trees to bear fruit outside their natural season. This study aims to analyze the impact of Off-Season technology on farming income, both directly and indirectly through production as a mediating variable. The research was conducted in Mekarjaya Village, Kertajati Subdistrict, involving 30 farmers who have adopted Off-Season technology. A quantitative approach was used, with descriptive analysis, simple linear regression, and path analysis as the data analysis techniques. The findings show that Off-Season technology has been adequately implemented by farmers, particularly in pruning, fertilization, the application of growth regulators, and pest control. Although the technology does not have a direct significant effect on income, it does show a significant indirect effect through increased production. The study concludes that production plays a crucial role in mediating the relationship between Off-Season technology and income enhancement in Gedong Gincu mango farming. Thus, the success of increasing farmers' income depends not only on the adoption of technology but also on production intensity, fruit quality, and selling prices during the off-season period.